KEGIATAN EKSTRAKURIKULER TARI UNTUK PENGUATAN IDENTITAS BUDAYA NUSANTARA DI SEKOLAH INDONESIA SINGAPURA - M. Rafli Akbar; Elindra Yetti; Ojang Cahyadi (Program Studi Pendidikan Tari FBS UNJ, 2024)
The aim of this research is to describe dance extracurricular activities to strengthen Indonesian cultural identity in Singapore Indonesian Schools. The theory used is the behaviorist theory explained by Gage and Berliner, namely that learning is a change in behavior caused by the interaction between stimulus and response. This research uses a qualitative approach with descriptive methods. Data was collected through observation, interviews and documentation. The results of this research are a description of the implementation of dance extracurricular activities at the Singapore Indonesian School, which includes the implementation of exercises and performances as a form of promoting Indonesian culture. This activity succeeded in strengthening Indonesian cultural identity among students through learning traditional dance and participating in Indonesian dance performances.